Pengaruh Independensi, Integritas, Pengetahuan, Pengalaman Kerja DanAkuntabilitas Terhadap Kualitas Audit(Studi Empiris Pada Auditor Bpkp Perwakilan Jawa Tengah) - Haryoto, Muhammad Febri, Dr. Triyono, S.E., M.Si (2017)
The purpose of this research examined the effect of independence, integrity, knowledge, job experience and accountability on audit quality auditor nBPKPrepresentatives of Central Java.The data is used primary data. This research was a quantitative approach.The sampling technique used was saturated sampling technique with 72respondents. Methods of collecting data using a questionnaire survey distributed to respondents. The data analysis technique used is multiple regression analysis.The results of this research shows that (1) independence not effect on auditquality, (2) integrity effect on audit quality, (3) knowledge effect on audit quality,(4) job experience not effect on audit quality 5) accountability effect on auditquality.